Microstructure, Mechanical Properties, and Corrosion Behavior of Boron Carbide Reinforced Aluminum Alloy (Al-Fe-Si-Zn-Cu) Matrix Composites Produced via Powder Metallurgy Route - Meignanamoorthy, M; Ravichandran, Manickam; Mohanavel, Vinayagam; Afzal, Asif; Sathish, T; Alamri, Sagr; Khan, Sher Afghan; Saleel, Ahamad C. (MDPI, 2021)
In this paper, Al-Fe-Si-Zn-Cu (AA8079) matrix composites with several weight percentages of B4C (0, 5, 10, and 15) were synthesized by powder metallurgy (PM). The essential amount of powders was milled to yield different compositions such as AA8079, AA8079-5 wt.%B4C, AA8079-10 wt.%B4C, and AA8079-15 wt.%B4C. The influence of powder metallurgy parameters on properties’ density, hardness, and compressive strength was examined. The green compacts were produced at three various pressures: 300 MPa, 400 MPa, and 500 MPa. The fabricated green compacts were sintered at 375◦C, 475 ◦C, and 575 ◦C for the time period of 1, 2, and 3 h, respectively. Furthermore, the sintered samples were subjected to X-ray diffraction (XRD) analysis, Energy Dispersive Analysis (EDAX), and Scanning Electron Microscope (SEM) examinations. The SEM examination confirmed the uniform dispersal of B4C reinforcement with the AA8079 matrix. The corrosion behavior of the composites samples was explored. From the studies, it is witnessed that the rise in PM process parameters enhances the density, hardness, compressive strength, and corrosion resistance.